Study on Experimental and Constitutive Model of Granite Gneiss under Hydro-Mechanical Properties - Lin Liu; Bo Wen (Applied Sciences, 2023)
Permeability, as a critical element in making sure the underground facilities are secure, is a vital consideration in analyzing the rock material seepage. Selecting granite gneiss from underground oil storage as the research sample in this study. Triaxial mechanical property tests under different hydro-mechanical properties were carried out under the rock full-automatic triaxial servo system that controls the application of axial pressure, confining pressure, and seepage pressure. Through experiments carried out, we obtained the rock samples’ mechanical properties and permeability in three stages of the stress–strain process. The study shows that the seepage pressure considerably affects granite gneiss strength and deformation parameters under hydro-mechanical properties. On the basis of the same confining pressure, in pace with the growth in seepage pressure, elastic modulus, the deformation modulus, and the peak strength present a prominent decreasing inclination. The derived mechanical parameters are bound up with the stages we divided. This study analyzes and discusses the relationship among the strains and permeability, establishing the granite gneiss hydro-mechanical coupling constitutive model. Verification shows the results in numerical and experimental matches well, indicating that the rock hydro-mechanical properties could be effectively represented by the constitutive model.